Temporal transcriptomic atlas reveals sequential engagement of classical and emerging regulated cell death pathways during PRRSV infection - Cao, Shinuo; Zhang, Li; Zhu, Rui; Nie, Nannan; Wu, Zhi; Zhu, Shanyuan (Frontiers in Veterinary Science, 2026)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes devastating economic losses through complex immunopathology, yet the molecular mechanisms orchestrating host cell fate remain elusive. Here we conducted temporal transcriptomic profiling of PRRSV-infected MARC-145 cells at 0, 12, 24, 36, 48, and 72 h post-infection, revealing the dynamic and temporally coordinated regulation of distinct regulated cell death (RCD) pathways. We discovered that PRRSV employs a sophisticated temporal strategy. The ferroptosis-related modules responsible for regulating lipid peroxidation (including ACSL4, LPCAT3, ALOX15, NOX1, and NCOA4) were largely downregulated, whereas cytoprotective elements (such as HSPB1, SLC40A1, HSPA5, GCLC, and later SLC7A11) were upregulated. Pathway scores remained negative up to approximately 48 h.p.i., gradually approaching neutrality by 72 h.p.i., suggesting that viral mechanisms may inhibit iron-dependent lethal lipid damage. Notably, we identified novel engagement of emerging RCD modalities-cuproptosis showed biphasic regulation with late activation through ATP7A/B suppression, while disulfidptosis signatures peaked at 36 h.p.i. via SLC3A2/SLC7A11 induction. Immunogenic cell death signatures persisted throughout infection with sustained HMGB1 elevation. These findings reveal PRRSV extensively modulates cell death transcriptional programs through temporally coordinated strategies: early inflammatory priming with lytic pathway suppression (12–24 h.p.i.), mid-phase ER stress and organellar remodeling (24–48 h.p.i.), and late metabolic and pH vulnerabilities (48–72 h.p.i.). These transcriptional profiles, pending functional validation, suggest how the virus may balance replication permissiveness with controlled cytopathology. These insights into temporal staging of RCD pathway modulation guide targeted interventions timed to specific infection phases to reduce disease while enhancing antiviral immunity.